The Role of Islamic Religious Education Teachers in Forming the Religious Character of Students at SMKN I Purwosari - Wahyu Ningtyas, Diah Ratna; Sholikhudin, M. Anang; Fachrudin Yusuf, Wiwin (Jurnal Pendidikan Indonesia, 2023)
The role of the PAI teacher in schools is very important in instilling and forming student character. One of the characters that must be formed, which is the basis of other characters is religious. Religious character is a character that shows that every thought, word and deed done by a person is always  based on divine values and the teachings of the religion he adheres to. Therefore, religious character is very important to be instilled in students in schools as places of formal education. The approach used in this research is descriptive qualitative. The process includes observation methods, interviews, and documentation. The results of this study indicate that: (1) The role of the PAI teacher in forming religious character through religious activities, (2) internal factors include within oneself and external factors, including family, friends, and social/environmental factors.